Inside-out: exploring prison culture - Alessia Morittu (Formare)
Prison culture encompasses the unwritten rules, values, behaviors, and power structures within correctional institutions, emerges from interactions among inmates, staff, and the broader societal context. This culture encompasses social hierarchies, unwritten behavioral codes, survival mechanisms, and attitudes towards correctional systems. Its influence extends to inmates’ behavior, perceptions, psychological well-being, and the dynamics of prison management. Studying prison culture is vital for identifying institutional gaps, enhancing safety and efficiency, supporting inmate rehabilitation, safeguarding human rights, and informing evidence-based criminal justice policies. This chapter examines the historical evolution of prison culture from the 1800s to today, exploring its elements, effects, and the challenges it poses. By analyzing these aspects, the chapter aims to foster a comprehensive understanding to guide humane and effective corrections practices.